Adaptive rotary tillage depth control with RBF-ADRC based on time-series prediction of tractor chassis pitch angle - Xuekai Huang; Xiaochan Wang; Yinyan Shi; Jing Yuan; Yanxin Wang; Lebin Lin; Jiajun Xu; Yongnian Zhang (Computers and Electronics in Agriculture, 2026)

Adaptive fuzzy coordinated control of orchard mowing robots using cutter torque-feedforward–SMC and chassis ICOA–Smith–RBF–PID strategies - Xuekai Huang; Zheng Wang; Xiaochan Wang; Yinyan Shi; Xiaopeng Huang; Bowei Wang; Lebin Lin; Yanxin Wang (Computers and Electronics in Agriculture, 2026)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

Transgenic Bt cotton driven by the green tissue-specific promoter shows strong toxicity to lepidopteran pests and lower Bt toxin accumulation in seeds - Qing Wang; Yi Zhu; Lin Sun; Lebin Li; Shuangxia Jin; Xianlong Zhang (Science China Life Sciences, 2016)